EDUCATIONAL SOFTWARE AND ARTIFICIAL INTELLIGENCE: STUDENTS' EXPERIENCES AND INNOVATIVE SOLUTIONS - Norbert Annuš (Інформаційні технології і засоби навчання)
The digitisation of education systems has been a growing trend in recent years. Artificial intelligence (AI) enables the development of new educational software that can even create adaptive - personalised learning plans for students. Such new software can be invaluable for improving the efficiency of the educational process, improving communication between teachers and students, and facilitating a better understanding of educational material. It is therefore important to make use of the tools already available in the educational process. Alongside teachers, students are the ones who are an integral part of the educational process and it is they who become active users of this software. The aim of our research is to assess students' interest in educational software. The study involved a quantitative survey involving a total of 500 students from different educational institutions covering primary, secondary and higher education, as well as Generation Z and Alpha. The survey gave students an insight into the concept of artificial intelligence. In addition to the openness to educational software, our study investigated the relationship between the students' attitudes towards artificial intelligence and their previous use of educational software. Our results show that students are keen to use educational software, and the majority are open to using artificial intelligence-based educational software. Our conclusions point to the need for educators to implement these software in their pedagogical practice whenever possible when shaping future teaching methods. Therefore, based on international literature, this study presents 15 educational software solutions that, through their intelligent features, accelerate and simplify the teaching process while supporting differentiated and more personalized education. The aim of this study is therefore to familiarise the reader with the potential of educational software and to encourage educational institutions and teachers to use this type of software on a daily basis.